Top Team Demographics, Innovation And Business Performance: Findings From English Firms And Cities, 2008-9 - Max Nathan (European Regional Science Association (ERSA), 2013)
High levels of net migration to the UK have contributed to growing cultural diversity, and researchers are turning their attention to the long-term effects of diversity on productivity. Yet little is known about these issues. This paper asks: what are the links between the composition of firms' top teams and business performance? What role do ethnic diversity and co-ethnic networks play? And do cities amplify or dampen these channels? I explore using a rich dataset of over 6,000 English firms. Owners, partners and directors set firms' strategic direction. Top team demography might generate production externalities through diversity (a wider range of ideas/ experiences, helping problem solving) and/or 'sameness' (via specialist knowledge or better access to international markets). These channels may be balanced by internal downsides (lower trust) and external barriers (discrimination), so that overall effects on business performance are unclear. In addition, urban locations (particularly big cities) may amplify any demographics-performance effects. I create a repeat cross-section of firms from the RDA National Business Survey. I construct measures of diversity and sameness across ethnicity and gender 'bases', alongside information on revenues, product and process innovation. I then regress these measures of business performance on top team demographics, plus firm level controls, area, year and detailed industry fixed effects. My results suggest a non-linear link between diversity and business performance, which is net positive for process innovation and net negative for turnover. Further tests on diverse and minority/female-headed firms find positive links for diverse top teams, negative for minority and female-only top teams. This implies that while diversity has internal and external benefits, penalties from being 'too diverse' probably result from external constraints. Further tests for intervening effects of capital cities, metropolitan hierarchies and urban form find some evidence of amplifying and dampening effects ? which are generally stronger in London and larger cities.
Keywords: J61; L21; M13; O11; O31; R23; 330; cities; innovation; entrepreneurship; cultural diversity; migration; gender